2013
DOI: 10.1016/j.ijdevneu.2013.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to bisphenol A interferes with the development of cerebellar granule neurons in mice and chicken

Abstract: In mice, prenatal exposure to low doses of bisphenol A has been shown to affect neurogenesis and neuronal migration in cortex, resulting in disturbance of both neuronal positioning and the network formation between thalamus and cortex in the offspring brain. In the present study we investigated whether prenatal exposure to bisphenol A disturbs the neurodevelopment of the cerebellum. Two different model systems were used; offspring from two strains of mice from mothers receiving bisphenol A in the drinking wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…Since the cellular effects of hormones are mostly mediated by their cognate receptors, this observation can explain why the biological effects of BPA-exposure could have remained masked or even unrecognised for a long time in spite of the dramatically increased transcriptional activity. Several studies suggested that exposure to EDs early in life leads to altered CNS development and functional deficiencies later in adulthood (Mathisen et al, 2013). The present results suggest that the final, al-tered outcome of hormonal signalling during ED exposure may only partly account for those anomalies, since the increased material and energy consumption by CNS cells in the process of enhanced transcription could also lead to energydeficient intracellular conditions that could be, at least in part, responsible for developmental deficiencies.…”
Section: Receptor Protein Levelsmentioning
confidence: 61%
“…Since the cellular effects of hormones are mostly mediated by their cognate receptors, this observation can explain why the biological effects of BPA-exposure could have remained masked or even unrecognised for a long time in spite of the dramatically increased transcriptional activity. Several studies suggested that exposure to EDs early in life leads to altered CNS development and functional deficiencies later in adulthood (Mathisen et al, 2013). The present results suggest that the final, al-tered outcome of hormonal signalling during ED exposure may only partly account for those anomalies, since the increased material and energy consumption by CNS cells in the process of enhanced transcription could also lead to energydeficient intracellular conditions that could be, at least in part, responsible for developmental deficiencies.…”
Section: Receptor Protein Levelsmentioning
confidence: 61%
“…In the human embryo, the external granule layer reaches its peak thickness by gestational week 25, and the process of migration continues well into the first postnatal year. In the chicken cerebellum, the migration of cerebellar granule neurons occurs prenatally (Aden et al, 2008(Aden et al, , 2011Volpe, 2009;Mathisen et al, 2013), in contrast to the situation in the rodent cerebellum where the external granule layer is formed postnatally, and granule neurons migrate between postnatal days 4 and 15 (Fujita, 1967). In fish, the migration of granule neurons follows yet a different pattern from that of mammals and chicken or is absent altogether (Butts et al, 2014).…”
Section: Expanding the Use Of The Chicken Embryo Modelmentioning
confidence: 96%
“…It is of particular benefit that the only endocrine influence the embryo receives from its mother is through the egg yolk. This facilitates external manipulation of the endocrine system and the study of whether pharmaceuticals and environmental chemicals cause endocrine disruption (Mathisen et al, 2013). Tight regulation of the endocrine system is crucial for correct development of the CNS.…”
Section: Expanding the Use Of The Chicken Embryo Modelmentioning
confidence: 99%
See 2 more Smart Citations